Education level inequalities and transportation injury mortality in the middle aged and elderly in European settings. Issue 3 (2nd June 2005) - Borrell, C; Plasència, A; Huisman, M; Costa, G; Kunst, A; Andersen, O; Bopp, M; Borgan, J-K; Deboosere, P; Glickman, M; Gadeyne, S; Minder, C; et al.
Abstract : Objective: To study the differential distribution of transportation injury mortality by educational level in nine European settings, among people older than 30 years, during the 1990s. Methods: Deaths of men and women older than 30 years from transportation injuries were studied. Rate differences and rate ratios (RR) between high and low educational level rates were obtained. Results: Among men, those of low educational level had higher death rates in all settings, a pattern that was maintained in the different settings; no inequalities were found among women. Among men, in all the settings, the RR was higher in the 30–49 age group (RR 1.46, 95% CI 1.32 to 1.61) than in the age groups 50–69 and ⩾70 years, a pattern that was maintained in the different settings. For women for all the settings together, no differences were found among educational levels in the three age groups. In the different settings, only three had a high RR in the youngest age group, Finland (RR 1.33, 95% CI 1.01 to 1.74), Belgium (RR 1.38; 95% CI 1.13 to 1.67), and Austria (RR 1.49, 95% CI 0.75 to 2.96). Conclusion: This study provides new evidence on the importance of socioeconomic inequalities in transportation injury mortality across Europe. This applies to men, but not to women. Greater attention should be placed on opportunities to select intervention strategies tailored to tackle socioeconomic inequalities in transportation injuries.